2020
DOI: 10.21203/rs.3.rs-49278/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

LncRNA LEF1-AS1/LEF1/FUT8 Axis Mediates Colorectal Cancer Progression by Regulating α1, 6-Fucosylation via Wnt/β-Catenin Pathway

Abstract: Background: Fucosylation alteration is involved in several steps of human cancer pathogenesis. Dysregulated long noncoding RNA (lncRNA) often leads to malignancy in colorectal cancer (CRC). Methods: Differential levels of LEF1-AS1, LEF1 and FUT8 are analyzed by qRT-PCR and western blot. Chip, RIP, EMSA and luciferase reporter assay confirm the direct interaction among LEF1-AS1, MLL1, H3K4me3, LEF1 and FUT8. Functionally, CRC cell proliferation, proliferation, migration and invasion are analyzed by CCK8 assay, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…They further explored the specific mechanism and established that LEF1-AS1 mainly acts through ceRNA on miR-489 to increase the DIAPH1 level (Cheng Y. et al, 2020). This is consistent with the findings of Qi et al (2021). In colon cancer, a series of cell experiments was conducted to verify the function of LEF1-AS.…”
Section: Colorectal Cancersupporting
confidence: 64%
See 3 more Smart Citations
“…They further explored the specific mechanism and established that LEF1-AS1 mainly acts through ceRNA on miR-489 to increase the DIAPH1 level (Cheng Y. et al, 2020). This is consistent with the findings of Qi et al (2021). In colon cancer, a series of cell experiments was conducted to verify the function of LEF1-AS.…”
Section: Colorectal Cancersupporting
confidence: 64%
“…They found that LEF1-AS1 may be beneficial to tumor growth and lung metastasis in vivo (Sun et al, 2020). Qi et al also confirmed the tumorigenic effect of LEF1-AS1 in colorectal cancer (Qi et al, 2021). In terms of HCC, in vivo experiments on tumor-bearing nude mice exhibiting positive WNK1 expression confirmed the interference effect of lncRNA LEF1-AS1 on HCC (Dong et al, 2020).…”
Section: In Vivo Studiesmentioning
confidence: 89%
See 2 more Smart Citations
“…A few studies focused on associations of FUT8 expression with other types of survival (DFS, RFS). For the research on pathways related to FUT8 and tumor survival, many references indicate that FUT8 activates several related signaling pathways, including Ras/MAPKK signaling, c-Met signaling, Akt/mTOR signaling and Wnt/β-catenin signaling, which ultimately lead to hepatocellular carcinoma or colorectal cancer affects the overall survival of patients [ 31 33 ]. Höti et al demonstrated that overexpression of FUT8 resulted in upregulation of epidermal growth factor receptor (EGFR) and corresponding downstream signaling, leading to increased prostate cancer cells survival [ 34 ].…”
Section: Discussionmentioning
confidence: 99%